2022
DOI: 10.1186/s13071-022-05421-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel theatre-based behaviour change approach for influencing community uptake of schistosomiasis control measures

Abstract: Background Appropriate behaviour change with regard to safe water contact practices will facilitate the elimination of schistosomiasis as a public health concern. Various approaches to effecting this change have been trialled in the field but with limited sustainable outcomes. Our case study assessed the effectiveness of a novel theatre-based behaviour change technique (BCT), in combination with cohort awareness raising and capacity training intervention workshops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Although BC was not the primary objective, it played an important and ongoing role in schistosomiasis control ( 10 ). Another study suggested that knowledge activates a belief system, affecting emotions, and subsequently leading to an intention to perform a specific behavior ( 11 ). Therefore, behavior intention is a necessary intermediate step in BC initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Although BC was not the primary objective, it played an important and ongoing role in schistosomiasis control ( 10 ). Another study suggested that knowledge activates a belief system, affecting emotions, and subsequently leading to an intention to perform a specific behavior ( 11 ). Therefore, behavior intention is a necessary intermediate step in BC initiatives.…”
Section: Introductionmentioning
confidence: 99%